Perancangan Door trim Mobil Sesuai Keinginan Pengguna City Car - Devy Kusumoningtyas Utami; Irwan Iftadi; D. Danardono D. P. (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
Nowadays, product design and development has been driven by market opportunity or known as market pull platform. Aimed to satisfy customer needs, this platform engaged customer at the first stage of the product design and development methods to be represented on the designing stage. The aim of this research is evolve driver door trim design of SmarT EV 2 with customer and ergonomic consideration. The proposed methods, based on combination solution of customers need, has arised four alternative design concepts to be assessed and selected. The choosen design as result is alternative design number four consist of power window and locks feature to enhace safety driving, retractable and electric mirror using knob, side pocket indue cup holder inside, gives dynamical sense by streamline-spherical countour design,and warped arm rest design with its panels layout that used and reached easily.